2016
DOI: 10.1111/febs.13543
|View full text |Cite
|
Sign up to set email alerts
|

A negative feedback loop between miR‐200b and the nuclear factor‐κB pathway via IKBKB/IKK‐β in breast cancer cells

Abstract: MicroRNAs (miRNAs) act as important post-transcriptional regulators of gene expression in diverse signalling pathways. However, the relationship between miR-200b and the nuclear factor-jB (NF-jB) signalling pathway remains poorly understood in breast cancer cells. In the current study, we show that IKBKB is a direct target of miR-200b, and that miR-200b downregulates IKBKB expression via directly binding to its 3 0 -UTR. miR200b inhibits IjBa phosphorylation, nuclear p50/p65 expression, NF-jBbinding activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 46 publications
(47 reference statements)
2
31
0
Order By: Relevance
“…Cyclin D1 participates in the G1 phase progression of the cell cycle in proliferating cells via the activation of cyclin dependent kinase 2 (CDK2), CDK4, or CDK6 [54]. Through the downregulation of IKBKB, miR-200b is also able to inhibit the activation of NF-κB, which suppresses breast cancer cell growth and migration [55]. In addition, the inactivation of NF-κB through the pentaerythritol tetranitrate-Akt-IKKβ axis results in lower cyclin D1 expression, suppressing renal cancer cell proliferation [56].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 participates in the G1 phase progression of the cell cycle in proliferating cells via the activation of cyclin dependent kinase 2 (CDK2), CDK4, or CDK6 [54]. Through the downregulation of IKBKB, miR-200b is also able to inhibit the activation of NF-κB, which suppresses breast cancer cell growth and migration [55]. In addition, the inactivation of NF-κB through the pentaerythritol tetranitrate-Akt-IKKβ axis results in lower cyclin D1 expression, suppressing renal cancer cell proliferation [56].…”
Section: Discussionmentioning
confidence: 99%
“…Quinn et al discussed the role of miR‐146a, miR‐221, miR‐579, miR‐125b, miR‐155, let‐7e, and miR‐98 in regulating the TLR4 signaling pathway during the development of endotoxin tolerance . mir‐15a, miR‐16, miR‐223, and miR‐23b bind to IKK‐α, while miR‐199a, MiR‐497, and miR‐200b bind to IKK‐β to inhibit the NF‐κB signaling pathway through regulation of the expression of IKK complex . MiR‐210 targets NF‐κB to inhibit the expression of posttranscriptional proteins and to reduce the binding of P50/P65 heterodimers and the promoter region of proinflammatory cytokines, thereby inducing endotoxin tolerance .…”
Section: The Molecular Mechanisms Of Endotoxin Tolerancementioning
confidence: 99%
“…NF‐κB pathway affects numerous processes, such as growth of cell, cancer metastasis, and inflammation. The NF‐κB signaling pathway is strongly influenced by miRNAs and has a major function in the tumorigenesis of diverse cancers, particularly breast tumor (Wu et al, ). Zhao et al () revealed the tumor suppressor role of miR‐29a is probably through controlling NF‐κB signaling pathway.…”
Section: Crosstalk Between Various Signaling Pathways and Mirnas In Bmentioning
confidence: 99%
“…Wu et al (2015) indicated that miR‐200b blocks NF‐κB via reducing the expression of (IKBKB)/IKK‐β and mutually, the inactivation of NF‐κB downregulates the miR‐200b transcription. Regarding the function of miR‐200b, it can offer an encouraging therapeutic goal for improving breast tumor management (Wu et al, ). The overexpression of specific miRNAs for example miR‐502‐5p chips in the reduction of TRAF2 gene expression in breast tumor.…”
Section: Crosstalk Between Various Signaling Pathways and Mirnas In Bmentioning
confidence: 99%